Effects of internal service quality on nurses' job satisfaction, commitment and performance: Mediating role of employee well‐being. Issue 2 (25th October 2020) - Abdullah, Muhammad Ibrahim; Huang, Dechun; Sarfraz, Muddassar; Ivascu, Larisa; Riaz, Amir
Abstract: Aim: The attitudes and behaviours of nursing staff are critical to determine patients' satisfaction and to have a competitive advantage for any healthcare organization. This study is set to investigate the effects of internal service quality (ISQ) on nurses' job satisfaction, employee commitment, well‐being and job performance in the healthcare sector of Pakistan. Further, this study also examines the mediating role of nurses' well‐being for the relationship of job satisfaction and commitment with their job performance. Methods: This was a cross‐sectional quantitative research. A self‐administered survey was used to collect data from 412 nursing employees of 20 private sector healthcare centres operating in Pakistan. Partial least square of structural equation model (PLS‐SEM) and structural equation modelling (SEM) were employed through Smart PLS 3.2.8 for data analysis. Results: Study results revealed that ISQ directly effects employees' satisfaction, commitment, well‐being of the nursing employees. Moreover, employees' well‐being has mediated job satisfaction and job performance relationship; however, well‐being did not mediate the relationship between commitment and job performance.